IFPRI Policy Seminar: Innovations in Measuring Women's Empowerment - Hogue, Emily; Quisumbing, Agnes R.; Alkire, Sabina (2012)
Policy Seminar Presentation with Emily Hogue, Agnes Quisumbing and Sabina Alkire on March 21, 2012